1995
DOI: 10.1002/j.1460-2075.1995.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Mop1-Mcs2 is related to mammalian CAK.

Abstract: The cyclin‐dependent kinase (CDK)‐activating kinase, CAK, from mammals and amphibians consists of MO15/CDK7 and cyclin H, a complex which has been identified also as a RNA polymerase II C‐terminal domain (CTD) kinase. While the Schizosaccharomyces pombe cdc2 gene product also requires an activating phosphorylation, the enzyme responsible has not been identified. We have isolated an essential S.pombe gene, mop1, whose product is closely related to MO15 and to Saccharomyces cerevisiae Kin28. The functional simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
82
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 53 publications
4
82
0
1
Order By: Relevance
“…The third cyclin gene, mcs2 ϩ , encodes an essential C-type cyclin that shares some of the characteristics of pch1 ϩ , the cyclin gene described in this study (18). Recent studies have shown that Mcs2 is the cyclin partner of Mcs6 kinase, which is also known as Crk1 or Mop1 (19,20). The Mcs2-Mcs6 kinase can carry out the activating threonine 167 phosphorylation of Cdc2 in vitro, although it is unknown whether it performs this function in vivo.…”
mentioning
confidence: 77%
“…The third cyclin gene, mcs2 ϩ , encodes an essential C-type cyclin that shares some of the characteristics of pch1 ϩ , the cyclin gene described in this study (18). Recent studies have shown that Mcs2 is the cyclin partner of Mcs6 kinase, which is also known as Crk1 or Mop1 (19,20). The Mcs2-Mcs6 kinase can carry out the activating threonine 167 phosphorylation of Cdc2 in vitro, although it is unknown whether it performs this function in vivo.…”
mentioning
confidence: 77%
“…LexA-Mcs6, LexA-Mcs2, and B42-Mcs2 were expressed in budding yeast from the pEG202 and pJG4-5 vectors, respectively [3]. To generate skp1-pJG4-5, the skp1 ORF was amplified by PCR with the following primers: ACG-CGT-CGA-CGG-ATC-CGA-ATT-CAC-CAT-GTC-CAA-AAT-CAA-ACT-GAT-TTC-ATC-T and TCC-CCC-GGG-CTC-GAG-CTA-TC T-GTC-TTC-GGC-CCA-TTC-AAT.…”
Section: Methodsmentioning
confidence: 99%
“…Protein amounts were estimated by silver staining and 100 ng of purified proteins was used for kinase assays. Bacterially expressed GST-CTD (a kind gift from David Chao and Richard Young) proteins were purified as described [3,35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations